MMP-9, brain edema, and length of hospital stay of patients with spontaneous supratentorial intracerebral hemorrhage after hematoma evacuation along with the administration of tigecycline (Medical Journal of Indonesia, 2016)
Background: The high plasma level of matrix metalloproteinses-9 (MMP-9) is believed to disrupt the blood-brain barrier (BBB) and cause brain edema, as well as increase patient's length of hospital stay (LOS). Tigecycline showed ability to reduce the MMP-9 level on study in animals. This study aimed to evaluate whether tigecycline can reduce the plasma levels of MMP-9; brain edema; and LOS of patients with supratentorial spontaneous intracerebral hemorrhage (SSICH). Methods: A randomized clinical trial (RCT) was conducted on 72 SSICH patients who underwent hematoma evacuation in eleven hospitals in Jakarta; 100 mg tigecycline (n=35) or 2 g fosfomycine (n=37) administered intravenously before skin incision as an prophylactic antibiotics to avoid post-operative infections. Plasma levels of MMP-9 were measured in all subjects before and on the first and seventh day after the surgery. Reduction of brain edema was assessed by comparing the extent of brain edema on computed tomography scan (CT scan) before and CT scan after surgery. The length of stay (LOS) was recorded at the time of hospital discharge either survive or death. Data were analyzed using Mann-Whitney and Chi-Square test. Results: There were non-significant statistical differences between two groups in the proportion of subjects with reduced MMP-9 levels on the first day (48% vs 50%; p=0.902; OR=1.1) and seventh day after the surgery (33% vs 48%; p=0.296; OR=1.9); proportion of the subjects with brain edema reduction (86% vs 80%, p=0.58); LOS (median 12 days vs 13 days, p=0.256; LOS ≥15 days 40% vs 27%; p=0.243; OR=1.81; NNT=8). Conclusion: On SSICH patients who underwent hematoma evacuation, tigecycline did not either reduce MMP-9 levels and brain edema or shorthen LOS.